The Influence of Internal Control System and HR Competence on the Quality of Financial Reports of PT. Bank Perkreditan Rakyat Mangatur Ganda - Dandi Sianipar; M. Irsan Nasution (Proceeding of The International Conference on Business and Economics, 2025)
This study is entitled "The Influence of Internal Control System and Human Resource Competence on the Quality of Financial Reporting at PT. Bank Perkreditan Rakyat Mangatur Ganda in Tanjung Morawa. This study aims to examine the influence of the internal control system and human resource competence on the quality of financial reporting at PT. Bank Perkreditan Rakyat Mangatur Ganda in Tanjung Morawa. This study is included in the associative research category which is conducted by distributing data through questionnaires to respondents of 30 employees at PT. Bank Perkreditan Rakyat Mangatur Ganda. The results of this study indicate that the internal control system and human resource competence have a significant effect on the quality of financial reporting. This shows that the better the internal control system and human resource competence, the better the quality of financial reporting produced.